Association between HLA-DQ alleles and Leprosy in Indonesia Javanese population - Hardyanto Soebono, Hardyanto Soebono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Previous studies showed that susceptibility to leprosy and antibody response toward M. leprae in Javanese population was under control of HLA-DR alleles. To investigate whether this susceptibility was also associated with HLA-DQ, the study had been continued with phenotyping of HLA-DQ alleles and antibody assay to the same population which consisted of 79 leprosy patients, 41 tuberculoid (TT/BT) and 38 lepromatous (LL/BL) type, and 50 healthy controls. The HLA-DQ typing had been performed by using a sequence specific oligonucleotyping (SSO). method, while the anti M. leprae antibody had been tested by ELISA and INHIBITION-ELISA.The results show that HLA-DQB501 is associated with leprosy, either tuberculoid or lepromatous type (OR 3.27; 95% Cl 1.42-7.60). When all HLA-DQ1 alleles are analyzed, a significant association is found only with lepromatous leprosy (OR 9.18; 95% Cl 1.89-86.30). IgG antibody anti 36 kD M. leprae is found to be associated with HLA-DQ102. The level of this antibody is higher in HLA-DQ102 positive individuals compared to those negative one (P). No correlation is found between HLA-DQ alleles and the seropositivity of either IgM or IgG.In conclusion, the susceptibility to leprosy in this population is also controlled by genes in HLA-DQ locus. This study also supports the previous findings that HLA-DQ1 is a universal marker for the susceptibility to lepromatous leprosy, while the infection with M. leprae per se is not controlled by HLA genetic factor.Key words : leprosy - M. /eprae - genetic factor - HLA-DQ - HLA-DQ1 - HLA-DQB501